Peppers: Vegetable and Spice Capsicums - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Peppers: Vegetable and Spice Capsicums Crop Production Science in Horticulture Series, No. 12. P Bosland and E Votava, New Mexico State University, USA. 1999. CABI Publishing. 216 pp. ISBN 0851993354. £27.50 $45 44.60 See earlier CABI refere